Variasi Pengadukan Dan Waktu Pada Pembuatan Bioetanol Dari Pati Sorgum Dengan Proses Sakarifikasi Dan Fermentasi Serentak (SSF) - Maulia Rayana; Chairul Chairul; Hafidawati Hafidawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sorghum is one of the agricultural commodities used for biofuels. Sorghum starch characteristics of high carbohydrate and contains high levels of starch as raw material potential of bioethanol. Making bioethanol done with simultaneous saccharification and fermentation process using yeast enzymes StargenTM 002 and Saccharomycess Cereviciae with varying speed agitation of 200, 250, 300 and 350 rpm and fermentation time 12, 24, 48, and 72 hours. The results of the analysis using a spectrophotometer and Alkoholmeter with highest bioethanol yield at speed agitation 350 rpm at 42 hours of fermentation with ethanol content of 8% (v/v) Keyword: Sorghum, Bioethanol, Enzym StargenTM 002, SSF, Speed Agitation